Axillary management in patients with clinical node-negative early breast cancer and positive sentinel lymph node: a systematic review and meta-analysis - Changzai Li; Pan Zhang; Jie Lv; Wei Dong; Baoshan Hu; Jinji Zhang; Hongcheng Zhu (Frontiers in Oncology, 2024)
BackgroundThe omission of axillary lymph node dissection (ALND) or axillary radiation (AxRT) remains controversial in patients with clinical node-negative early breast cancer and a positive sentinel lymph node.MethodsWe conducted a comprehensive review by searching PubMed, Embase, Web of Science, and Cochrane databases (up to November 2023). Our primary outcomes were overall survival (OS), disease-free survival (DFS), locoregional recurrence (LRR), and axillary recurrence (AR).ResultsWe included 26 studies encompassing 145,548 women with clinical node-negative early breast cancer and positive sentinel lymph node. Pooled data revealed no significant differences between ALND and sentinel lymph node biopsy (SLNB) alone in terms of OS (hazard ratio [HR]0.99, 95% confidence interval [CI] 0.91-1.08, p=0.84), DFS (HR 1.04, 95% CI 0.90-1.19, p=0.61), LRR (HR 0.76, 95% CI 0.45-1.20, p=0.31), and AR (HR 1.01, 95% CI 0.99-1.03, p=0.35). Similarly, no significant differences were observed between AxRT and SLNB alone for OS (HR 0.57, 95% CI 0.32-1.02, p=0.06) and DFS (HR 0.52, 95% CI 0.26-1.05, p=0.07). When comparing AxRT and ALND, a trend towards higher OS was observed the AxRT group (HR 0.08, 95% CI 0.67-1.15), but the difference did not reach statistical significance (p=0.35, I2 = 0%). Additionally, no significant differences significance observed for DFS or AR (p=0.13 and p=0.73, respectively) between the AxRT and ALND groups.ConclusionOur findings suggest that survival and recurrence rates are not inferior in patients with clinical node-negative early breast cancer and a positive sentinel lymph node who receive SLNB alone compared to those undergoing ALND or AxRT.